2008
DOI: 10.1111/j.1540-8175.2007.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Performance Index Correlates with Right Ventricular Ejection Fraction Measured by Nuclear Ventriculography

Abstract: MPI greater than 0.50 indicates that RV function is abnormal and a value of PTASV > 17.25 cm/sec indicates normal RV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Meluzin et al (2001), reported that an S' velocity less than 11.5 cm/s was predictive of a RV dysfunction with a sensitivity of 90% and a specificity of 85%. [29] MPI was found to correlate with radionuclide derived RVEF in earlier studies [30].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Meluzin et al (2001), reported that an S' velocity less than 11.5 cm/s was predictive of a RV dysfunction with a sensitivity of 90% and a specificity of 85%. [29] MPI was found to correlate with radionuclide derived RVEF in earlier studies [30].…”
Section: Discussionmentioning
confidence: 89%
“…In a study done by Fan et al in (2005), S' found to be significantly reduced in patients with proximal RCA lesion and RV-MI as compared to those with non-proximal RCA lesion (7.0 ± 2.0 cm/s vs. 8.7 ± 1.9 cm/s, p < 0.01). RV Tei index in patients with proximal RCA lesion and RV-MI also increased as compared to those with non-proximal RCA lesion (0.65 ± 0.19 vs. 0.40 ± 0.15; p< 0.01) [31].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of MPI to quantitatively assess RV function is validated in adults and patients with congenital heart disease [85,86]. In addition, MPI has demonstrated prognostic power in differentiating outcome in RV failure [87][88][89][90]. Care should be taken in using MPI for congenital heart disease with altered loading conditions.…”
Section: Mpimentioning
confidence: 99%
“…Its comparison with invasive measurements makes the index a sensitive indicator of RV function. This index, also named Tei index, is not influenced by heart rate, body weight, and aging and is correlated with %RVEF obtained by nuclear ventriculography [30]. Tei index can be also obtained using tissue doppler imaging (TDI) [31].…”
Section: Rv Myocardial Performance Indexmentioning
confidence: 99%